Characterizing the effects of titanium dioxide and silver nanoparticles released from painted surfaces due to weathering on zebrafish (Danio rerio). Issue 4 (21st April 2021) - Mittal, Krittika; Rahim, Arshath Abdul; George, Saji; Ghoshal, Subhasis; Basu, Niladri
Abstract: Silver (nAg) and titanium dioxide nanoparticles (nTiO2 ) are common engineered nanoparticles (ENPs) added into paint for their antimicrobial and whitening properties, respectively. Weathering of outdoor painted surfaces can release such ENPs, though little is known about the potential effects of released ENPs on aquatic species. The objective of this study was to characterize the toxicity of nAg and nTiO2 released from painted panels using fish liver cells (CRL2643) and zebrafish embryos (OECD 236 embryotoxicity test). Cells and embryos were exposed to suspensions of pristine nAg or nTiO2, panels (unpainted or painted with nAg or nTiO2 ) or base paint, after sonication. Cell viability and gene expression were assessed using resazurin assay and qPCR, respectively, while embryo mortality and deformities were scored visually via microscopic examination. In the cell studies, both paint-released nanoparticles did not affect viability, but paint-released nAg resulted in differential expression of a few genes including gclc and ncf1 . In embryos, paint-released nAg increased mortality and incidence of deformities, whereas paint-released nTiO2 resulted in differential expression of several genes including gclc, ncf1, txnrd1, gpx1b, and cyp1c1 but without major phenotypic abnormalities. Comparing the two types of exposures, paint-released exposures affected both molecular (gene expression) and apical (embryotoxicity) endpoints, while pristine exposures affected the expression of some genes but had no apical effects. The differing effects of paint-released and pristine nanoparticle exposures suggest that further research is needed to further understand how paint coatings (and the products of their weathering and aging) may influence nanoparticle toxicity to aquatic organisms.